Optimal design of the roof structure of the 2,000-seat tributary of the rowing channel. - Xolqo‘ziyeva Madina Eshpo‘lat qizi; Jamolova Mohigul Xudoyberdi qizi; Boqiyev Sulaymon Vahobovich (Genius Journals, 2022)
The article proposes that the roof of the rowing canal's 2000-seat grandstand be designed using the best alternative among the commonly utilized trusses. The usage of parallel-belt, single-angle trusses has been proved to be effective in the design of such trusses. The grandstand is meant to be 24x80 meters in size.
Keywords: Roof-Covering; Truss; Interval; Base